Silver-impregnated external-ventricular-drain-related cerebrospinal fluid infections: a meta-analysis. Issue 3 (March 2016) - Atkinson, R.A.; Fikrey, L.; Vail, A.; Patel, H.C.
Summary: Background: Cerebrospinal fluid (CSF) infection is the primary complication associated with placement of an external ventricular drain (EVD). The use of silver-impregnated EVD catheters has become commonplace in many neurosurgical centres. Aim: To assess the effect of silver-impregnated EVD catheter usage on catheter-related CSF infections. Methods: A meta-analysis was performed by systematically searching Medline, Embase and the Cochrane Library. All randomized controlled trials (RCTs) and non-RCTs comparing silver-impregnated and plain EVD catheters were identified and analysed. Findings: Six non-RCTs were included. The crude infection rate was 10.8% for plain catheters and 8.9% for silver-impregnated catheters [pooled odds ratio (OR) 0.71, 95% confidence interval (CI) 0.46–1.08; P  = 0.11]. In a microbiological spectrum analysis, silver-impregnated catheters demonstrated a significantly lower rate of CSF infections caused by Gram-positive organisms (2.0% vs 6.7% in the silver-impregnated and plain catheter groups, respectively; pooled OR 0.27, 95% CI 0.11–0.63; P  = 0.002). Conclusion: The antimicrobial effects of silver-impregnated EVD catheters may be selective, and may need to be evaluated further in a prospective, controlled manner.